Clinico-pathologic profile and pattern of p53 expression of lung adenocarcinoma in non-smokers and smokers in a tertiary cancer centre - Khan N. S., Parwin; P., Sindhu Nair; Sukumaran, Renu; A. L., Lijeesh; K., Jayasree (International Journal of Research in Medical Sciences, 2024)
Background: Lung cancer is the most common cause of cancer mortality worldwide. Smoking is undoubtedly the major risk factor of lung cancer in both genders. Adenocarcinoma is the most common form of lung cancer in both men and women and the most prevalent subtype in non-smokers. Lung cancer in never-smokers is a distinct entity with sparse studies. We studied the clinico-pathologic profile of lung adenocarcinoma and pattern of p53 expression in smokers and non-smokers. Methods: A prospective study involving 100 lung adenocarcinoma cases from January 2020 to June 2021 examined p53 expression using immunohistochemistry. Trucut biopsies, fine needle aspiration cytology (FNAC) cell blocks, and pleural effusion were analyzed to identify the predominant morphological subtype of the lung adenocarcinoma. Results: The most common histological pattern of lung adenocarcinoma was solid, and the presenting symptoms were cough and dyspnoea in both smokers and non-smokers. The incidence of lung adenocarcinoma was higher in non-smokers in the study. p53 expression had a significant correlation with smoking but not with stage of disease or morphological subtype of lung adenocarcinoma. Conclusions: p53 mutation has a statistical correlation with smoking in adenocarcinomas in our population. Among the adenocarcinoma cases in our study, non-smokers predominate (n=53). Even though our study showed the p53 mutation has no statistical correlation with the stage of the disease or histological subtype in adenocarcinoma, more cases need to be studied to prove this observation.